The Ethiopic Homily on Holy Easter attributed to John Theologos and its Arabic Vorlage (CPG 4163.2) - Butts, Aaron Michael; Erho, Ted (Aethiopica, 2023)
In the standard reference works for Ethiopian and Eritrean studies, one finds a Homily on Holy Easter (CAe 1265) attributed to Gregory of Nazianzus and identified as one of his Orations (CPG 3010). Both the attribution and identification are, however, incorrect. Rather, this Homily on Holy Easter, which is actually attributed to an otherwise unknown John Theologos in the earliest recoverable layer of the Ethiopic tradition, is to be identified as an Ethiopic version of a homily, recorded as CPG 4163.2, attested in two Arabic manuscripts, one where it is attributed to Ephrem and the other where it is anonymous.